The word of the Lord in Jeremiah - Thomson, J.G.S.S.; Tyndale Fellowship for Biblical Research; Tyndale Old Testament Lectures (London, UK Tyndale, 1959)
Inlcudes bibliographical references.
Delivered in Cambridge on July 2nd, 1959 at a meeting convened by the Tyndale Fellowship for Biblical Research
Keywords: Bible. O.T. Jeremiah -- lectures, sermons, addresses, etc